Disc Laser System Construction and Characterization - Abd-Alameer, Yousif H.; Dhahir, Mohamed K.; Hajim, Khalil I. (Iraqi Journal of Laser, 2010)
In this work a Nd:YVO4 thin disc laser setup is designed and fabricated. The disk laser system is designed to be compact. The laser crystal was pumped by a 808 nm diode laser. The effect of input current and pulse frequency on the output energy at pulse operation mode, and the effect of the input current on the output power at CW mode operation are tested. At the pulsed mode, the output energy increased linearly with the input current and decreased with pulse frequency. The threshold current increased with increasing pulse frequency increasing. The maximum output energy from the thin disc laser was 0.98 μJ at 1.3 kHz frequency, with 0.49A. A minimum threshold current for CW mode of operation. The maximum output power from the disc laser was 22 mW.